Оподаткування у рамках правового режиму Дія Сіті: спеціальний податковий режим - Kotenko, Artem M (Problemi zakonnostì, 2024)
The relevance of the article is due to the study of theoretical and practical problems of creating separate conditions of taxation within the Diia City legal regime and the continuation of the study of tax regimes. The purpose of the article is to analyze the provisions of the tax legislation regulating the specifics of taxation within the Diia City legal regime with a view of establishing a special tax regime (regimes). To achieve the objectives of the study, a combination of methods was used, including dialectical and formal-legal approaches. The structural-functional approach allowed for a deeper exploration of the system of characteristics of special tax regimes. Empirical data obtained from open sources were utilized during the research. The methods and approaches applied ensured a comprehensive examination of the issues related to special tax regimes and their substantive features. The author analyzes the provisions of tax legislation that define the peculiarities of taxation of Diia City residents and Diya City specialists. It has been established that the conditions of taxation under the Diia City legal regime provide for the possibility of applying a corporate income tax rate of 9% to a separately defined tax base. Taxation has been shifted to operations aimed at a capital gains which is a capital gains tax. For this the provisions of Section 3 "Corporate income tax" were changed, but not the provisions of Section 14 "Special tax regimes" of the Tax Code. It turns out that the legal regime of Diia City also provides for a different procedure for taxation. Taxation conditions of resident specialists are fixed in Section 4 "Income Tax of Individuals" of the Tax Code. According to the requirements of Tax Code Diia City resident specialists cannot be subject to the special tax regime. Established that there is no characteristics of the special legal regime, except for the possibility of establishing it for business entities. It appears that the formal criteria do not allow to classify the taxation procedure within the Diia City legal regime as a special tax regime. The content of the specifics of taxation within the Diia City legal regime indicates precisely the special regime of taxation.